Synthesis, molecular modeling and NAD(P)H:quinone oxidoreductase 1 inducer activity of novel 2-phenylquinazolin-4-amine derivatives. (1st November 2016) - Ghorab, Mostafa M.; Alsaid, Mansour S.; Higgins, Maureen; Dinkova-Kostova, Albena T.; Shahat, Abdelaaty A.; Elghazawy, Nehal H.; Arafa, Reem K.
Abstract: Reactive oxygen species (ROS) play an integral role in the pathogenesis of most diseases. This work presents the design and synthesis of novel 2-phenylquinazolin-4-amine derivatives (2 –12 ) and evaluation of their NAD(P)H:quinone oxidoreductase 1 (NQO1) inducer activity in murine cells. Also, molecular docking of all the new compounds was performed to assess their ability to inhibit Keap1–Nrf2 protein–protein interaction through occupying the Keap1–Nrf2-binding domain which biologically leads to a consequent Nrf2 accumulation and enhanced gene expression of NQO1. Docking results showed that all compounds have the ability to interact with Keap1; however compound7, the most active compound in this study, showed more interactions with key amino acids.